2006
DOI: 10.1590/s0100-83582006000100015
|View full text |Cite
|
Sign up to set email alerts
|

Tuberização de dois cultivares de batata sob aplicação de sulfoniluréias

Abstract: A resposta de plantas de batata à simulação de contaminação de tanques de pulverizadores com sulfoniluréias foi avaliada em experimento em vasos, em Águas da PrataSP, 2004. O objetivo deste trabalho foi avaliar o efeito de subdoses de metsulfuron-methyl, nicosulfuron e sulfometuron-methyl em dois cultivares de batata quanto à produção e qualidade dos tubérculos. Metsulfuron-methyl, nicosulfuron e sulfometuron-methyl foram aplicados em pós-emergência em plantas de batata dos cultivares Atlantic e Lady Rosetta. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 4 publications
(5 reference statements)
0
4
0
2
Order By: Relevance
“…) on potatoes, Novo & Miranda Filho (2006) found that with increasing dose there was a reduction in fresh pasta of normal tubers and of the total tubers and increase in fresh mass of abnormal tubers. Furthermore, sulfometuron-methyl residues in the soil from 240 parts per trillion (ppt) resulted in potato tubers deformation such as cracks and folds (Hutchinson et al, 2007).…”
Section: Resultsmentioning
confidence: 94%
“…) on potatoes, Novo & Miranda Filho (2006) found that with increasing dose there was a reduction in fresh pasta of normal tubers and of the total tubers and increase in fresh mass of abnormal tubers. Furthermore, sulfometuron-methyl residues in the soil from 240 parts per trillion (ppt) resulted in potato tubers deformation such as cracks and folds (Hutchinson et al, 2007).…”
Section: Resultsmentioning
confidence: 94%
“…Nos sistemas de cultivo de batata, o emprego de produtos químicos é prática considerada obrigatória na defesa fitossanitária (Novo & Miranda Filho, 2006) e pode ter determinado os menores teores de Cmic nos sistemas CCB e CBAM. Esses baixos teores de Cmic nesses sistemas podem ser atribuídos tanto ao intensivo manejo do solo, característico do cultivo de batata, como também ao uso frequente de agrotóxicos.…”
Section: Resultsunclassified
“…There are reports associating the cracking of tubers to the presence of ALS-inhibiting herbicides (acetolactate synthase) such as nicosulfuron, metsulfuron and tribenuron, EPSPs-inhibiting herbicide (5-enolpyruvylshikimate-3-phosphate synthase) such as glyphosate and auxin mimics such as dicamba and clorpyralid (Eberlein et al, 1994;Wall, 1994;Novo & Miranda Filho, 2006;Hutchinson et al, 2014). No reports were found linking HPPD inhibitor herbicides to any physiological disorder in potato tubers.…”
Section: Discussionmentioning
confidence: 99%
“…Soils contaminated with herbicide residues reduce the yield of potato crops according to the cultivar used (Novo & Miranda Filho, 2006) due to the phenomenon known as herbicide carryover. Physiological disorders and the decline in the yield were observed due to sulfonylureas and imidazolinones (Eberlein & Guttieri, 1994;Eberlein, Westra, Harderlie, Withmore, & Guttieri, 1997;Novo & Miranda Filho, 2006), to auxin mimics (Wall, 1994) and to glyphosate (Hutchinson, Felix, & Boydston, 2014), even at very low concentrations in the soil (for example, nicosulfuron 0.15 mg ha -1 ) or due to treatment drift of areas adjacent to the potato crops.…”
Section: Introductionmentioning
confidence: 99%